2014
DOI: 10.1007/s40822-014-0004-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additional monetary tightening on exchange rates

Abstract: Since the global financial crisis, Central Banks have used various policy tools to sustain financial stability besides price stability. Additional Monetary Tightening is one of these tools that the Central Bank of the Republic of Turkey used in 2011-2012. The effects of this tool on the exchange rate are the main theme of this paper. Our analysis indicates that additional monetary tightening has a significant role in reducing volatility in the exchange rate. It is also shown that during the days of additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The analyses conducted throughout the previous papers suggest that the new policy framework effectively contributed to financial stability. For example, Ermişoğlu, Akçelik, Oduncu and Taşkın (2013) argued that the extra monetary constricting by the CBRT had an important role in the decline of fluctuation in the exchange rate and appreciating the Turkish Lira against the rising market currencies. Oduncu et al (2013c) found out that the new structure of monetary policy that incorporates interest rate path, the strategy of liquidity funding, and demanded funds after 2010 contributed to Turkey's financial stability by lessening the credit growth volatility.…”
Section: New Monetary Policy Frame and Reserve Option Mechanism-rommentioning
confidence: 99%
“…The analyses conducted throughout the previous papers suggest that the new policy framework effectively contributed to financial stability. For example, Ermişoğlu, Akçelik, Oduncu and Taşkın (2013) argued that the extra monetary constricting by the CBRT had an important role in the decline of fluctuation in the exchange rate and appreciating the Turkish Lira against the rising market currencies. Oduncu et al (2013c) found out that the new structure of monetary policy that incorporates interest rate path, the strategy of liquidity funding, and demanded funds after 2010 contributed to Turkey's financial stability by lessening the credit growth volatility.…”
Section: New Monetary Policy Frame and Reserve Option Mechanism-rommentioning
confidence: 99%
“…In Turkey, the policymaking institutions have opted to use various measures to manage short-term capital flows to the country in an unconventional monetary policy framework (Aysan et al, 2014). Specifically, the Central Bank of Turkey has put into implementation numerous macroprudential tools, such as required reserve ratios (RRRs) and reserve option mechanism (ROM), to tame domestic credit growth (see Alper et al, 2012;Akçelik et al, 2013;Ermisoglu et al, 2014;Aysan et al, 2015b). Table 1 presents the details of macroprudential policies in the country in a chronological order.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…The record of this policy framework is mixed. On the positive side, the interest rate corridor, active liquidity management and the ROM have been shown to reduce exchange rate volatility (Akçelik et al, 2012;Ermişoğlu et al, 2013;Oduncu, et al, 2013a). Değerli and Fendoğlu (2013), in addition, find that the ROM reduced volatility, skewness and kurtosis of exchange rate expectations, implying that tail risks of large exchange rate swings associated with sharp movements in capital flows have diminished.…”
mentioning
confidence: 99%